2021
DOI: 10.1016/j.ejso.2021.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for rectal cancer: Differences in resection rates among hospitals in the Netherlands

Abstract: Aim: Numerous quality improvement initiatives for rectal cancer surgery have focused on textbook outcome parameters. In these studies, resection rate and patients who did not undergo surgery are not included, but these parameters might help to evaluate the surgical care for rectal cancer. The aim of this study is to assess the variation of non-metastatic rectal cancer resection rates among hospitals and its effect on patient outcomes. Methods: All patients diagnosed with non-metastatic rectal cancer between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…The study was based on a retrospective real-world study; we inevitably encounter the problem of controlling confounding factors. The present study suggested the distribution of the age, differentiated grade, T stage, N stage, M stage, and metastatic organ number showed marked differences between the patients with and without surgery, which was consistent with the previous studies [15,16]. Many methods such as multivariable Cox regression and instrumental variable method were recommended to adjust the effect of these confounding factors.…”
Section: Discussionsupporting
confidence: 91%
“…The study was based on a retrospective real-world study; we inevitably encounter the problem of controlling confounding factors. The present study suggested the distribution of the age, differentiated grade, T stage, N stage, M stage, and metastatic organ number showed marked differences between the patients with and without surgery, which was consistent with the previous studies [15,16]. Many methods such as multivariable Cox regression and instrumental variable method were recommended to adjust the effect of these confounding factors.…”
Section: Discussionsupporting
confidence: 91%
“…Those authors who did report providing feedback fed the results into quality improvement efforts at the regional (9; 39%) or national (6; 27%) level, sent the results to all studied groups (4; 18%), or both sent the results to all studied groups and fed the results into quality improvement efforts (3; 13%). Notably, only one of the 22 studies advocated for public reporting of their outcomes 39 . The feedback of all other studies was explicitly for the use of healthcare systems.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, only 22 studies (25%) reported notifying those providing the data of the variation they detected or otherwise using the results to inform quality improvement efforts. Only one study advocated for public reporting of their findings 39 . The majority of these quality indicators were derived from high-income settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study suggested the distribution of the age, differentiated grade, T stage, N stage, M stage, and metastatic organ number showed marked differences between the patients with and without surgery, which was consistent with the previous studies. 17 , 18 Many methods such as multivariable Cox regression and instrumental variable method were recommended to adjust the effect of these confounding factors. However, none of these methods alone could entirely avoid the bias.…”
Section: Discussionmentioning
confidence: 99%